La ocupación humana del territorio de la comarca del río Guadalteba (Málaga) durante el Pleistoceno - Cabello Ligero, Lidia (Archaeopress archaeology., 2017)
This investigation exhaustively gathers the archaeological evidence of the Palaeolithic human settlement in the Guadalteba river region (Malaga, Spain) during the Pleistocene. The main objective is to show the direct relationship between the reservoirs and the sources of raw materials, located in the fluvial terraces, in the geological outcrops and in the surface deposits.